2018
DOI: 10.2503/hrj.17.87
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Radial Fruit Cracking by Single Spraying of Forchlorfenuron (1-(2-chloro-4-pyridyl)-3-phenylurea) of Fruit Clusters in Tomato Production under Rain Shelter

Abstract: This study clarified suitable times for the single spraying of a fruit cluster with forchlorfenuron (1-(2-chloro-4-pyridyl)-3-phenylurea, CPPU) to reduce radial fruit cracking during tomato production under a rain shelter. We examined the relation between fruit development at the time of CPPU spraying and the occurrence of radial fruit cracking. The rate of occurrence was reduced in fruits that had been sprayed when they were 1.5-6.5 cm in diameter. The CPPU spraying time was regarded as the time when the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Fruit cracking is typically linked to the various rates at which the fruit and its peel expand. An increase in cell counts close to the fruit epidermis is associated with a decrease in fruit cracking caused by CPPU (Sano et al 2018) [24] .…”
Section: Fruit Quality Parametersmentioning
confidence: 99%
“…Fruit cracking is typically linked to the various rates at which the fruit and its peel expand. An increase in cell counts close to the fruit epidermis is associated with a decrease in fruit cracking caused by CPPU (Sano et al 2018) [24] .…”
Section: Fruit Quality Parametersmentioning
confidence: 99%
“…Matsuo et al (2012) suggested that cytokinins (CK) are involved in cell division during tomato fruit development by applying a synthetic CK, forchlorfenuron (1-(2-chloro-4-pyridyl)-3-phenylurea, CPPU), to unpollinated tomato ovaries to induce parthenocarpic fruit development. A single spraying of CPPU on tomato fruit clusters (fruit size: 3.0-4.9 cm diameter) reduced fruit cracking as a result of an increase in the number of cells near the epidermis (Sano et al, 2018).…”
Section: External Appearance Of the Fruit And Exocarp Pigment Distributionmentioning
confidence: 99%